Analisis Pelanggaran Garis Sempadan Sungai di Perumahan Wahyu Utomo Ngaliyan Semarang - Muhammad Haidar; Alfin Miftah Rozak (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
Where all these studies and research were carried out aimed at evaluating and reawakening the community to care more about development regulations because in fact all forms of rules such as the GSS and others aim to prosper the community, especially in the development sector so that they are neatly arranged without neglecting the surrounding environment.